The anthropometry of children and adolescents may be influenced by the prenatal smoking habits of their grandmothers: A longitudinal cohort study. Issue 6 (18th August 2014) - Golding, Jean; Northstone, Kate; Gregory, Steven; Miller, Laura L.; Pembrey, Marcus
<x xml:space="preserve">Abstract</x> Objectives Previously, in the Avon Longitudinal Study of Parents and Children (ALSPAC), we have shown different sex‐specific birth anthropometric measurements contingent upon whether or not prenatal smoking was undertaken by paternal grandmother (PGM±), maternal grandmother (MGM±), and the study mother (M±). The findings raised the question as to whether there were long‐term associations on the growth of the study children over time. Methods Measures of weight, height, body mass index, waist circumference, lean mass, and fat mass of children in the ALSPAC study from 7 to 17 years of age were used. We compared growth in four categories at each age: PGM+M− with PGM−M−; MGM+M− with MGM−M−; PGM+M+ with PGM−M+; MGM+M+ with MGM−M+; and adjusted for housing tenure, maternal education, parity, and paternal smoking at the start of the study pregnancy. Results We found that if the PGM had, but the study mother had not, smoked in pregnancy, the girls were taller and both genders had greater bone and lean mass. However, if the MGM had smoked prenatally but the mother had not (MGM+M−), the boys became heavier than expected with increasing age—an association that was particularly due to lean rather than fat mass, reflected in increased strength and fitness. When both the maternal grandmother and the mother had smoked (MGM+M+) girls had reduced height, weight, and fat/lean/bone mass when compared with girls born to smoking mothers whose own mothers had not smoked (MGM−M+). Conclusions This study indicates that smoking in humans can have sex‐specific transgenerational effects. Am. J. Hum. Biol. 26:731–739, 2014. © 2014 The Authors American Journal of Human Biology Published by Wiley Periodicals, Inc.